Vonoprazan-Based Third-Line Therapy Has a Higher Eradication Rate against Sitafloxacin-Resistant Helicobacter pylori - Saito, Yoshimasa; Konno, Kaho; Sato, Moeka; Nakano, Masaru; Kato, Yukako; Saito, Hidetsugu; Serizawa, Hiroshi (Cancers, 2019)
Eradication of Helicobacter pylori (H. pylori) is an effective strategy for preventing various gastrointestinal diseases such as gastric cancer and mucosa-associated lymphoid tissue (MALT) lymphoma. However, the eradication success rate is decreasing because of a recent increase in drug-resistant strains of H. pylori. Here, we evaluated the success rate of eradication therapy with vonoprazan (VPZ), a new potassium-competitive acid blocker, against drug-resistant H. pylori. In total, 793 patients who received H. pylori eradication therapy were investigated retrospectively. All underwent esomeprazole (EPZ)-based triple therapy (n = 386) or VPZ-based triple therapy (n = 407) for first-, second- and third-line H. pylori eradication for 7 days. The overall success rates of first- and third-line H. pylori eradication were significantly higher for VPZ-based triple therapy (88.4% and 93.0%, respectively, per protocol (PP)) than for EPZ-based triple therapy (69.5% and 56.5%, respectively, PP). Moreover, the success rates of first- and third-line eradication of clarithromycin (CLR)- and sitafloxacin (STFX)-resistant H. pylori were significantly higher for VPZ-based triple therapy (72.0% and 91.7%, PP) than for EPZ-based triple therapy (38.5% and 20.0%, PP). In addition, patient age did not affect the eradication rate of VPZ-based first-line therapy, whereas the success rate of EPZ-based therapy was lower in patients under 65 years of age. Our results clearly demonstrated that VPZ-based therapy achieved a higher eradication rate even against CLR- and STFX-resistant H. pylori, and that patient age did not affect the eradication rate of VPZ-based therapy. These findings suggest that dual therapy using VPZ and amoxicillin may be sufficient for standard H. pylori eradication, and may thus also be beneficial for avoiding antibiotic misuse.